1997
DOI: 10.1103/physrevb.55.6440
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effects and energy barrier distribution on the magnetic relaxation of nanocrystalline hexagonal ferrites

Abstract: The static and dynamic magnetic properties of nanocrystalline BaFe 10.4 Co 0.8 Ti 0.8 O 19 M -type doped barium ferrite were studied in detail to clarify the effect of interactions on the magnetic relaxation of an assembly of small particles. The logarithmic approximation was unable to account for the magnetic relaxation of the sample. Interaction effects were analyzed from the low-field susceptibility, ⌬M plots and the time dependence of thermoremanence, indicating that demagnetizing interactions led to an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 50 publications
5
57
2
Order By: Relevance
“…This change of behavior in the effective energy barrier distributions has been observed experimentally in ensembles of Ba ferrite fine particles, 33,45 in which evidence of T ln͑t / 0 ͒ scaling of the relaxation curves was demonstrated and the relevance of demagnetizing interactions in this sample was established by means of Henkel plots at different T. In this experiment, the authors also studied relaxation processes after different cooling fields and found that when increasing the cooling field, the effective distributions changed from a function with a maximum that extends to high energies to a narrower distribution with a peak at much lower energy scales for high cooling fields. The effective distribution at high H FC , which was there argued to be given by the intrinsic anisotropy barriers of the particles, appears shifted towards lower energy values with respect to the anisotropy distribution as derived from TEM due to the demagnetizing dipolar fields generated by the almost aligned spin configuration induced by the H FC .…”
Section: Effective Energy Barrier Distributions From T Ln"t / 0 …supporting
confidence: 64%
“…This change of behavior in the effective energy barrier distributions has been observed experimentally in ensembles of Ba ferrite fine particles, 33,45 in which evidence of T ln͑t / 0 ͒ scaling of the relaxation curves was demonstrated and the relevance of demagnetizing interactions in this sample was established by means of Henkel plots at different T. In this experiment, the authors also studied relaxation processes after different cooling fields and found that when increasing the cooling field, the effective distributions changed from a function with a maximum that extends to high energies to a narrower distribution with a peak at much lower energy scales for high cooling fields. The effective distribution at high H FC , which was there argued to be given by the intrinsic anisotropy barriers of the particles, appears shifted towards lower energy values with respect to the anisotropy distribution as derived from TEM due to the demagnetizing dipolar fields generated by the almost aligned spin configuration induced by the H FC .…”
Section: Effective Energy Barrier Distributions From T Ln"t / 0 …supporting
confidence: 64%
“…The The low-field susceptibility ͑200 Oe͒ displayed a wide maximum in the ZFC curve at ca. 205 K and a flattened FC curve below this temperature, 15 being T 0 ϭϪ170Ϯ30 K, the value of the Curie temperature extrapolated from the reciprocal susceptibility, 15 which indicates strong interparticle interactions. Taking into account the aggregation state of the powder samples, direct exchange through the surface of neighboring particles and dipolar interactions are present.…”
mentioning
confidence: 99%
“…In particular, they display high closure fields with high values of the differential susceptibility and shifts in the hysteresis loops after field cooling [3,4,5,6] whose origin is still a matter of controversy. While some of these features have been attributed the existence of dipolar interactions among the particles [7,8,9,10], there are experimental evidences that finite-size and surface effects are crucial in order to understand this phenomenology. In this study, we present the results of Monte Carlo (MC) simulations of the magnetic properties of individual nanoparticles which aim at clarifying what is the specific role played by increased radial anisotropy at the surface on the magnetization processes.…”
Section: Introductionmentioning
confidence: 99%